The Influence of Price and Promotion on Customer Interest in Using Pawn Products at PT. Pegadaian UPC Kabar Kabupaten Lombok Timur - Kulsum, Umi; Siti Ahdina Saadatirrohmi (Jurnal Perbankan Syariah, 2024)
This research aims to determine the effect of price and promotions on customer interest in using pawn products at PT. Pegadaian UPC Kabar in East Lombok District. There is a fact that the number of customers using pawn products is decreasing. This research uses quantitative research methods with data collection techniques using observation and questionnaires. The number of samples used in this research was 96 respondents from customers PT. Pegadaian UPC Kabar. The sampling technique used was purposive sampling. The data obtained was processed using SPSS 26 with data analysis techniques used, namely validity test, reliability test, classical assumption test, multiple linear analysis test, t test (partial), f test (simultaneous) and coefficient of determination test. The results of the research conducted show that price have no partial effect on customers' interest in using pawn products and promotions have a partial effect on customers' interest in using pawn products. Simultaneously, price and promotions influence customer interest in using pawn products at PT. Pegadaian UPC Kabar in East Lombok Regency with an influence level of 15.5% and 84.5% is influenced by factors other than price and promotions as seen from the R-Square test results.